Effects of resveratrol on eNOS in the endothelium and the perivascular adipose tissue. Issue 1 (3rd July 2017) - Xia, Ning; Förstermann, Ulrich; Li, Huige
Abstract: Under physiological conditions, nitric oxide (NO) is produced in the vasculature mainly by the endothelial NO synthase (eNOS). Experiments using gene‐disrupted mice have demonstrated that eNOS has antihypertensive, antithrombotic, and antiatherosclerotic effects. Recent studies show that eNOS is expressed not only in the endothelium but also in the perivascular adipose tissue (PVAT). Resveratrol prevents eNOS uncoupling and upregulates eNOS expression and activity. These effects of resveratrol are well established for the eNOS enzyme in the endothelium. Interestingly, resveratrol also improves PVAT function. However, a causal role for eNOS in the effects of resveratrol on PVAT function has not yet been verified and needs to be studied in the future.